FORMAL AND CASUAL SPEECH STYLES IN STUDENT PRESENTATIONS - Abdul Rifki S. Ngou; Nadia A. Naki; Wahyu Maladjai; Muziatun Muziatun (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study looks at how students use formal and casual ways of speaking during their presentations in the classroom. The study aims to recognize the features of formal speaking style and examine how students use informal speaking style during their academic presentations. This research used a descriptive qualitative method and looked at it through a sociolinguistic lens. The information was gathered from a video of a classroom presentation held by second-semester students in the English Education Program. The researcher looked at what students said during their presentation times. This included their opening talks, explaining the materials, asking and answering questions, and interacting with their classmates. The study looked at Martin Joos’ ideas about different ways of speaking, especially paying attention to formal and casual styles. The results indicate that students often used a formal way of speaking at the beginning, while explaining their materials, and when wrapping up their presentations. They did this by using polite phrases, well-structured sentences, and academic words. At the same time, a casual way of talking came up during conversations and interactions with classmates. This included using informal phrases, mixing different languages, and communicating in a laid-back manner. Many things affected how speech styles were used, such as the mood in the classroom, the connection with the audience, the students' confidence, and the subjects they were presenting on. The research also discovered that a relaxed way of speaking helped students feel less anxious, connect better with others, and explain topics more clearly. But using too many casual phrases can lower the academic quality of presentations. So, students should find a good balance between formal and casual ways of speaking when they communicate in school. This research backs up the idea in sociolinguistics that the way we use language varies based on the social situation and the goals of our communication.